Pengaruh Gaya Kepemimpinan terhadap Kepuasan Kerja Karyawan pada KPKNL Manado - Kawengian, Deddy; Areros, William Agustinus; Wonokh, Jan (JURNAL ADMINISTRASI PUBLIK, 2015)
This study aims to: To determine the influence of significant between leadership style on employee job satisfaction the State Property Office and Auction Manado. This study used quantitative descriptive method using a simple correlation analysis. Measurement of the population in this study are employees of the State Property Office and Auction Manado totaling 40 people. The result of analysis can product moment coefficient that is equal to 0.718 which shows the significant correlation or relationship between leadership style on employee job satisfaction. With the results of this means there is a leadership style had a strong influence and significant impact on employee satisfaction the State Property Office and Auction Manado Keywords: leadership style, job satisfaction